Strategie inwestycyjne i wyniki finansowe funduszy hedgingowych - Pruchnicka-Grabias, Izabela (Hedge Funds as Long-term Investments, 2007)
The author analyzes the profitability of hedge funds investments between 1994 and 2005 and presents various investment styles used by these institutions. It is emphasized that although hedge funds generate negative long-term rates of return very rarely, they do not have to be always higher than those of stock indexes, because the overall effect depends both on the economic situation on the financial market and the right choice of a hedge fund, as their investment styles are totally different.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 312-319